PENGARUH PENDAPATAN PREMI, HASIL UNDERWRITING, HASIL INVESTASI DAN RISK BASED CAPITAL TERHADAP LABA PERUSAHAAN ASURANSI UMUM SYARIAH - nurul hidayati nasution; satria tri nanda (Universitas Lancang Kuning, 2020)
This study was conducted to test the effect of premium income, underwriting results, investment income and risk based capital on general syariah insurance companies’ profit. The method applied in this study was quantitative method. The population included the insurance companies registered at Otoritas Jasa Keuangan ( OJK) in 2011-2015. The samples of this study were 1 syariah insurance companies and 14 unit syariah Insurance companies selected using purposive sampling technique. The types of data used on this study was secondary data. The method of data collection applied was documentation method and panel data regression using a computer program Eviews 7.0. The results of the analysis showed that: (1) premium income had significant positive effect on insurance profit, (2) underwriting results had significant negative effect on insurance profit, (3) inverstment income had negative significant effect on insurance profit, (4) risk based capital had positive significant effect on insurance profit.